If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(-1x) + -1x = 9 + -1x Remove parenthesis around (-1x) 3 * -1x + -1x = 9 + -1x Multiply 3 * -1 -3x + -1x = 9 + -1x Combine like terms: -3x + -1x = -4x -4x = 9 + -1x Solving -4x = 9 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -4x + x = 9 + -1x + x Combine like terms: -4x + x = -3x -3x = 9 + -1x + x Combine like terms: -1x + x = 0 -3x = 9 + 0 -3x = 9 Divide each side by '-3'. x = -3 Simplifying x = -3
| 2=-3/2(-1)+b | | -3x-4y(-0.5+-0.75x)=2 | | 13x+1=13x+27 | | 20a=180 | | 5(2x+1)-3(x-4)=3x+1 | | 6X-33=6X+33 | | 4x+1=(11) | | 0.3(r+2)=0.1(2r-4) | | 3x+2-5x=7+3x | | 2/3(6x-3y)-1/2(2x-4y) | | n/2+6.5=0 | | -4y+8=3y-8 | | 1/2+t=2/3 | | 2(p-1)=15 | | 2x=(-12) | | x/6=12/4 | | x+4/30=4/6 | | x/6+12/4 | | Y=30+0.85Y+20+55 | | 7k+m^2=13-5km | | (x^2+1)=0 | | 4x+3=3-(x-2) | | 2x=30-4x | | 10+3x-7x=-34 | | 7t=2 | | 2x-2.9=13.1-6x | | n/5-10=3 | | 3x+5=2(2x-2) | | 2p+10=4p | | 6x-x+10=15-7x-5 | | x-6=(-7) | | 2m+6/2 |